Climate change, 'technology' and gender: "Adapting women" to climate change with cooking stoves and water reservoirs in rural Nicaragua - Gonda, Noemi (Swedish University of Agricultural Sciences, 2017)
Presented by Noemi Gonda on 15 June 2017, as part of the webinar 'Gender, climate change and agriculture'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).